Viral Proteases and Antiviral Protease Inhibitor Therapy Proteases in Biology and Disease - Lendeckel, Uwe; Hooper, Nigel M. (Proteases in Biology and Disease, 2009)
The 8th volume in the Proteases in Biology and Disease series focuses on the role of proteases in virus function and their potential as anti-viral targets. Viral infections are still difficult to threat and some remained life-threatening diseases in spite of antiviral drug research over decades. Proteases are still regarded as an Achilles' heel of the pathogens and, thus, protease inhibitors may help to handle the known and the emerging viral threads. The book discusses viral proteases of the most important pathogenic viruses, responsible for severe diseases: AIDS, SARS, Hepatitis, Cytomegalovirus, T-cell lymphotropic virus, Picornavirus. This book focuses specifically on the viral proteases, crucial prerequisites for viral entry into cells and viral replication. Viral proteases represent an important pharmaceutical target. The current stage of protease inhibitor development and therapy are summarised and discussed by experts in the field. This volume represents a timely and valuable continuation of the Proteases in Biology and Disease series. The reader will learn the potential for proteases as targets for effective anti-virals. This book will be a valuable source of information on viral proteases and provoke further research in this important field.